SIMULATOR BOILER HYBRID SEBAGAI FUNGSI PENGERING DAN PENGOLAH LIMBAH MEDIS JENIS PLASTIK - Liputo, Burhan; Djamalu, Yunita; Umela, Syaiful; Gobel, Leni; Djafar, Romi (Program Vokasi-Universitas Negeri Gorontalo, 2024)
The hybrid boiler simulator is a simulation machine designed with two working functions, namely as a medical waste processing function and as a drying cabinet function. As a medical waste processor, this machine will focus on plastic medical waste, and as a dryer function, this machine will be a clothes-drying tool or cabinet. So based on the multifunctionality of the machine, this system has hybrid working characteristics. Hybrid boiler simulators can be a solution, providing the function of processing plastic medical waste and providing the advantageous function of economical and environmentally friendly drying. Therefore, this research aims to create a hybrid boiler simulator that can be used as a plastic medical waste processing machine and also as a clothes drying machine. The hybrid boiler system is designed by applying the concept of appropriate technology so that its implementation can be done easily and practically. The research implementation method is a classification of plastic medical waste, concept design, and analysis, construction design of a hybrid boiler system combined with an incinerator for burning medical waste, system function testing, and observation of test data. The focus of his research is the heat of burning plastic waste, heat radiation, circulators, and flow control systems as well as the characteristics of the results of burning plastic waste. The results of this research are that the hybrid boiler simulator machine can function as an incinerator machine to burn plastic medical waste and function as a clothes dryer; The function of the incinerator in this machine is only through two processes, namely the process of burning plastic medical waste raw materials and the process of burning carbon gas or smoke produced from the process of burning raw materials; the sumulator machine is not yet equipped with a fogging process for the function of smoke cleaning filter and fogging control; the hybrid boiler simulator machine works on the principle of automatic control based on temperature detection using a temperature sensor; The combustion temperature in the boiler machine can be controlled at a standard of 830 °C and the drying room temperature can be set at a room temperature of 50 – 150 °C.